2021
DOI: 10.3389/fcell.2020.635783
|View full text |Cite
|
Sign up to set email alerts
|

Plastin 3 in X-Linked Osteoporosis: Imbalance of Ca2+-Dependent Regulation Is Equivalent to Protein Loss

Abstract: Osteogenesis imperfecta is a genetic disorder disrupting bone development and remodeling. The primary causes of osteogenesis imperfecta are pathogenic variants of collagen and collagen processing genes. However, recently variants of the actin bundling protein plastin 3 have been identified as another source of osteogenesis imperfecta. Plastin 3 is a highly conserved protein involved in several important cellular structures and processes and is controlled by intracellular Ca2+ which potently inhibits its actin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…Different variants in PLS3 , which is ubiquitously expressed in solid tissues, lead to decreased bone mineral density [ 22 ]. Previous findings suggest that the majority of the OI-linked PLS3 pathogenic variants are either loss-of-function changes (nonsense or frameshift varaints) which rarely result in translated protein products due to nonsense-mediated mRNA decay [ 16 , 23 ]. Separately, a rare single nucleotide polymorphism of the PLS3 gene was reported in association with osteoporosis in postmenopausal women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different variants in PLS3 , which is ubiquitously expressed in solid tissues, lead to decreased bone mineral density [ 22 ]. Previous findings suggest that the majority of the OI-linked PLS3 pathogenic variants are either loss-of-function changes (nonsense or frameshift varaints) which rarely result in translated protein products due to nonsense-mediated mRNA decay [ 16 , 23 ]. Separately, a rare single nucleotide polymorphism of the PLS3 gene was reported in association with osteoporosis in postmenopausal women [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Different variants in PLS3 have shown differences in distribution between lamellipodia and focal adhesions [ 16 ]. Studies on the chicken homolog of the PLS3 gene have shown that the function of its protein product can be linked to mechanosensitivity of osteocytes [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations in PLS3 lead to severe X-linked hereditary osteoporosis with bone fragility [25][26][27][28][29][30][31][32][33][34][35] . Congenital osteoporosis develops upon deletion and truncations in PLS3 gene (reviewed in 36 ), but also due to point mutations resulting in PLS3 variants, which either lose the ability to bundle F-actin or display perturbed sensitivity to Ca 2+ 37 . By contributing to endocytosis 38 and migration, PLS3 plays neuroprotective roles by lessening the toxicity of pathogenic poly-glutamine-containing proteins 39 , alleviating symptoms of spinal muscular atrophy 40,41 , and coordinating neuronal cell migration in embryogenesis 42 .…”
Section: Introductionmentioning
confidence: 99%